2019
DOI: 10.3390/ijfs7030038
|View full text |Cite
|
Sign up to set email alerts
|

Does Death Anxiety Moderate the Adequacy of Retirement Savings? Empirical Evidence from 40-Plus Clients of Spanish Financial Advisory Firms

Abstract: This three-wave study analyses the mediating role of financial behavior in the relationship between financial goals and retirement saving adequacy, and the moderating role of Death anxiety. The participants in the study (N = 276) were 40-plus Spanish clients of financial advisory firms. The results show that the relationship between financial goals and retirement saving adequacy is, in fact, mediated by financial behavior. We also found that death anxiety moderates the financial behavior-retirement saving adeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Additionally, death anxiety has been defined as a complex emotional response triggered by illness and the proximity of death. As previous research has shown [ 93 ], death anxiety could impinge on a lot of life spheres, like consumer behavior, finances, and also work-related behavior. In this vein, future studies could deeply explore the potential role of these variables in the willingness of RTW among survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, death anxiety has been defined as a complex emotional response triggered by illness and the proximity of death. As previous research has shown [ 93 ], death anxiety could impinge on a lot of life spheres, like consumer behavior, finances, and also work-related behavior. In this vein, future studies could deeply explore the potential role of these variables in the willingness of RTW among survivors.…”
Section: Discussionmentioning
confidence: 99%
“…This financial behaviour for retirement planning involves the use of economic notions (Sherraden et al, 2011), that finally supposes to personal financial capacity, which must be understood as the implementation of financial knowledge. In addition, emotional factors could affect financial goals and retirement savings (Garmendia et al, 2019;Osborne, 2016).…”
Section: Personal Finance Management For Retirement By a Complete Modelmentioning
confidence: 99%